2019
DOI: 10.12669/pjms.35.1.249
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis Internal jugular vein versus Subclavian vein Catheters: Complications, patients’ comfort, tolerance and cost-effectiveness

Abstract: Objective: To compare hemodialysis (HD) internal jugular vein (IJV) versus subclavian vein (SCV) catheters in terms of procedural complications, patients’ comfort, tolerance and cost effectiveness. Methods: Sixty six consecutive eligible adult patients planned for hemodialysis @ 3 sessions/ week for maximum 42 days in a private hospital at Sialkot, Pakistan were documented between March 2017 and April 2018. A group, IJV or SCV catheter was allotted to alternate subjects. The catheters were inserted as pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…As previously described, over the years, an enormous amount of research comparing AxV/SCV and IJV has focused on the complications and safety of these two insertion approaches. However, patient satisfaction and comfort were only mentioned in only a few studies [ 19 , 20 ]. In this prospective randomized controlled study, we compared patients’ comfort of IVAP implantation as primary outcome measure, and this is the first study to put patient comfort in the forefront.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, over the years, an enormous amount of research comparing AxV/SCV and IJV has focused on the complications and safety of these two insertion approaches. However, patient satisfaction and comfort were only mentioned in only a few studies [ 19 , 20 ]. In this prospective randomized controlled study, we compared patients’ comfort of IVAP implantation as primary outcome measure, and this is the first study to put patient comfort in the forefront.…”
Section: Discussionmentioning
confidence: 99%
“…Quitting the study by one participant is unexpected as such practice is observed in interventional trials. 13,14 However, female predominance is just on the basis of predominance of this gender in college roll. Coincidently, females are more vulnerable to the effects than males.…”
Section: Discussionmentioning
confidence: 99%
“…SC CVC is undesirable when alternative VA are available 6 but some centres advocate for use of SC CVC as the CVC of choice. 8 A high incidence of SC CVC could also be due to recall errors of the patients as they may not distinguish between SC and IJ. The patients preferred AVF over other forms of VA as long-term VA and most of the patients ultimately converted to AVF over other forms of VA. For this reason, 90.47% of the participating patients had AVF at the time of the study.…”
Section: Discussionmentioning
confidence: 99%